Patient outcomes following minimally invasive plate osteosynthesis for fractures of the distal tibia - Baskey, Somnath; Nayak, Manmatha; Khatua, Jugaratna; Patra, Gopabandhu (International Journal of Research in Orthopaedics, 2025)
Background: Minimally invasive plate osteosynthesis (MIPO) has become the go-to method for treating fractures of distal tibia because of its several benefits over open procedures. Assessing the radiological and clinical results of participants undergoing MIPO to treat fractures of distal tibia was the main goal of this study. Methods: The study was prospective-observational. It was conducted at Srirama Chandra Bhanja (S.C.B.) medical college and hospital, Cuttack, India for one year, i.e., from February 2024 to January 2025. This study included fifty-two individuals who had received MIPO for fractures of the distal tibia. Results: Among all the 52 patients who participated in the study, 33 (63.4%) were men and 19 (36.5%) were women. A mean age of 52.3±6.5 years was found. Most of the patients, i.e., 38 (73.1%) of patients took 20-24 weeks. Six (11.5%) of patients took >24 weeks. And, lastly, 08 (15.4%) of patients took <20 weeks. Conclusions: According to the study’s findings, MIPO for distal tibia fractures produces good radiological and clinical outcomes, with the majority of patients having a strong functional recovery and union within 24 weeks.